Optimisation Of Quality Performance Parameters For Digital Dental Cone Beam Computed Tomography (Cbct) System - Anthony, Rabba James (2023)
The cone beam computed tomography (CBCT) system has been widely used in dental imaging for various dentomaxillofacial applications. A standardised testing protocol for evaluation of a wide range of CBCT performance and image quality parameters is still limited and the commercially available testing tool is unaffordable by some centres. This study aims to evaluate the performance parameters and optimise the quality assurance (QA) test for digital dental CBCT system.